PENGOLAHAN LIMBAH PLASTIK MENJADI PAVING BLOCK DESA PEMATANG JOHAR KECAMATAN LABUHAN DELI KABUPATEN DELI SERDANG - Ferdi Aldiansyah,; Haris Fahmi Harahap,; , Intan Lidia Defega,; Rinsa Oos,; Reza Hanafi Lubis, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service activity, which is located in Pematang Johar village, generally aims to instill a strong personality in students regarding leadership, responsibility, entrepreneurship, as well as increase student empathy and concern directly with the community. In this activity, the focus of attention is helping the community find solutions to various problems, one of which is the management of waste and plastic waste. Based on the results of surveys, interviews, and observations made to the Pematang Johar village community, especially in hamlet XV, Pematang Johar village, that public awareness of waste management is very minimal and there is a lot of plastic waste piling up which can have a negative impact on health and disrupt the preservation of environmental functions, both residential areas, forests, rice fields, and rivers. To reduce the volume of plastic waste that is not managed properly, an effort is made to utilize plastic waste for the manufacture of Paving Blocks. The method used in the effort to manage plastic waste is by providing counseling and assistance to the community about the process of managing plastic waste